Classical philology and theology: entanglement, disavowal, and the godlike scholar - Conybeare, Catherine; Goldhill, Simon (Cambridge University Press, 2021)
Modern disciplinary silos tend to separate the fields of classical philology and theology. This collection of essays, however, explores for the first time the deep and significant interactions between them. It demonstrates how from antiquity to the present they have marched hand in hand, informing each other with method, views of the past and structures of argument. The volume rewrites the history of discipline formation, and reveals how close the seminar is to the seminary.